2022
DOI: 10.1111/jonm.13546
|View full text |Cite
|
Sign up to set email alerts
|

Relationships among basic psychological needs, organizational commitment, perceived authentic leadership and turnover intention in Korean nurses: A cross‐sectional study

Abstract: Aim: This study determined the relationships of satisfaction and frustration with basic psychological needs, organizational commitment, perceived authentic leadership and turnover intention in nurses in South Korea.Background: Minimizing nurse turnover is essential for improving the quality of nursing care and patient safety.Methods: This was a cross-sectional, correlational pilot study of 216 nurses at a university hospital in South Korea. Data were collected with a self-report questionnaire, from 1 to 15 Sep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 32 publications
(45 reference statements)
1
14
0
Order By: Relevance
“…Strict leaders reported by more than 40% of the nurses were also related to the highest increment in turnover intention. Leadership is considered as a predictable factor in nurses' intention to leave (Hwang et al, 2022; Wu et al, 2020). Our finding lent support to previous nursing research that the experience of working under a toxic leader may cause significant stress in nurses and have tendencies to leave their profession (Labrague et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Strict leaders reported by more than 40% of the nurses were also related to the highest increment in turnover intention. Leadership is considered as a predictable factor in nurses' intention to leave (Hwang et al, 2022; Wu et al, 2020). Our finding lent support to previous nursing research that the experience of working under a toxic leader may cause significant stress in nurses and have tendencies to leave their profession (Labrague et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Rebuilding our health care systems with relational integrity and ethical practice environments is needed (Ulrich et al, 2020). Hwang et al found that authentic nurse leadership had a significant effect on nurses' turnover intention (Hwang et al, 2022) and suggests it is foundational to a healthy work environment. Developing nurse leaders with relational competencies and perhaps using both conceptual frameworks as organisational models is indicated.…”
Section: Implications For Nursing Managementmentioning
confidence: 99%
“…A study conducted in Turkey found that nurses' normative commitment, affective commitment, and continuance commitment was slightly above average (Akgerman & Sönmez, 2020). Studies conducted in Taiwan (Chang, 2015), Egypt (Elkady et al., 2021), and South Korea (Hwang et al., 2022) found that nurses had a medium organizational commitment. A study found that nurses' normative commitment has the highest mean in public hospitals, and nurses' continuance commitment was the highest mean in non‐public hospitals (Elkady et al., 2021).…”
Section: Discussionmentioning
confidence: 99%